Significant preservation of swallowing function in chemoradiotherapy for advanced head and neck cancer by prophylactic swallowing exercise. Issue 4 (16th June 2015) - Ohba, Shinichi; Yokoyama, Junkichi; Kojima, Masataka; Fujimaki, Mitsuhisa; Anzai, Takashi; Komatsu, Hiroaki; Ikeda, Katsuhisa
Abstract: Background: Dysphagia is a serious complication of chemoradiotherapy (CRT) in patients with head and neck cancer. Approximately 20% to 30% of patients who have dysphagia require feeding tubes. The purpose of this study was to evaluate the impact of prophylactic swallowing exercises on swallowing function. Methods: Fifty‐one patients with advanced oropharyngeal, hypopharyngeal, and laryngeal cancers were included in this study. Twenty‐one patients performed the Shaker exercise and 30 practiced traditional Mendelsohn maneuvers (control group). Before and after treatment, videofluoroscopy and swallowing motion were analyzed to establish movement of the hyoid bone, larynx, and aspiration scores. Results: Average movement of the hyoid bone, thyrohyoid shortening, and upper esophageal sphincter opening were significantly better maintained in the Shaker group. Aspiration score of the Shaker exercise was significantly lower than control group. Feeding tube rates for the Shaker and control groups were 14% and 40% ( p < .05). Conclusion: Shaker exercises as a prophylactic exercise contributed to preservation of swallowing function in patients with head and neck cancer. © 2015 Wiley Periodicals, Inc. Head Neck 38: 517–521, 2016